Protocol: A Multiplexed Reporter Assay to Study Effects of Chromatin Context on DNA Double-Strand Break Repair - Schep, Ruben; Leemans, Christ; Brinkman, Eva K.; van Schaik, Tom; van Steensel, Bas (Frontiers in Genetics, 2022)
DNA double-strand breaks (DSBs) can be repaired through various pathways. Understanding how these pathways are regulated is of great interest for cancer research and optimization of gene editing. The local chromatin environment can affect the balance between repair pathways, but this is still poorly understood. Here we provide a detailed protocol for DSB-TRIP, a technique that utilizes the specific DNA scars left by DSB repair pathways to study pathway usage throughout the genome. DSB-TRIP randomly integrates a repair reporter into many genomic locations, followed by the induction of DSBs in the reporter. Multiplexed sequencing of the resulting scars at all integration sites then reveals the balance between several repair pathways, which can be linked to the local chromatin state of the integration sites. Here we present a step-by-step protocol to perform DSB-TRIP in K562 cells and to analyse the data by a dedicated computational pipeline. We discuss strengths and limitations of the technique, as well as potential additional applications to study DNA repair.